Collective reflective assessment for shared epistemic agency by undergraduates in knowledge building. (2nd March 2020) - Yang, Yuqin; Chen, Qianqian; Yu, Yawen; Feng, Xueqi; van Aalst, Jan
Abstract: We examined the facilitation of shared epistemic agency through a knowledge‐building (KB) design that included analytics‐supported collective reflective assessment (AsCRA). Forty undergraduate students taking a Liberal Studies course at a university in central China used the promising ideas tool and the knowledge building discourse explorer to self‐analyze the online discourse they had created in Knowledge Forum® (KF), an online discourse environment; 34 students in a comparison section of the same course used KF but did not use the additional tools. Both classes were taught by the same teacher and studied the same inquiry topics. Multifaceted analysis of students' interaction in and the quality of discourse on KF, an educational online platform, indicated that analytics‐supported reflective assessment helped them to develop high‐level shared epistemic agency in the KB process. Qualitative analysis showed that AsCRA helped students to focus on high‐level goals (idea negotiation, synthesis of ideas and rise above thinking) in KB, and to engage in continuous assessment, reflection, and action planning to regulate and improve their discourse. The findings have important implications for the design of technology‐rich environments to support learners, and may help teachers identify the potential uses of such environments to encourage learners to engage in productive collaborative inquiry and develop metacognition and agency.